A DESCTIPTIVE ANALYSIS ON THE KAKULA MUSIC PLAYING PATTERNS AS TRADITIONAL MUSIC OF THE KAILI TRIBE OF CENTRAL SULAWESI PROVINCE - Bawiling, Rifaldo Christein; Sri Hartati, R. A. Dinar; Takalumang, Luccylle M. (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research is intended to provide an overview of the Kakula Music Playing Pattern as a Traditional Music of the Kaili Tribe of Central Sulawesi Province. Kakula is a traditional music of Kaili tribe (native tribe of Central Sulawesi. The method used in this research is a descriptive qualitative research method in which this research is carried out with data collection techniques using observation, interview and documentation methods. The findings show that Kakula as the music instrument have a long history with the people of Kaili Tribe. The Kakula music have various functions for the people of Kaili Tribe. Hence, Kakula is a form of presentation of ensemble music with rhythmic patterns that are different from one another.